Circuit analysis II : with MATLAB applications - Karris, Steven T. (Orchard Publications, 2003)
This text is a sequel to Circuit Analysis I, ISBN 0-9744239-3-9. Includes the following topics: Second Order Circuits, Resonance, Elementary Signals, The Laplace Transformation and its Inverse, Circuit Analysis with Laplace Transforms, Frequency Response and Bode Plots, Self and Mutual Inductances, Transformers, One and Two Port Networks, Three Phase Systems, Introduction to MATLAB, Differential Equations, Matrices and Determinants, Constructing Semilog Plots with Microsoft Excel, Scaling.